A Virtual Firewall Mechanism Using Army Nodes to Protect Cloud Infrastructure from DDoS Attacks - Jeyanthi N; Mogankumar P. C. (Cybernetics and Information Technologies, 2014)
Cloud is not exempted from the vulnerability of Distributed Denial of Service (DDoS) attack, a serious threat to any distributed network and has considerably less effective solutions to deploy in the network. This paper introduces a novel mechanism to protect and prevent the cloud from the spurious packets targeting the depletion of server resources. The army nodes called “Cloud DDoS Attack Protection” (CDAP) nodes are installed at the cloud server farm/ Datacenter (DC). These army nodes act as virtual firewall without destroying the Cloud Infrastructure and improve the availability of DC, even at the time of DDoS attack. By continuously monitoring the incoming packets, CDAP filters the attack packets intruding the Cloud DC. Availability is further improved by handing over the threat detection and attack mitigation to CDAP nodes and by redirecting the malicious user requests to the dump network. The simulation results prove that the introduction of CDAP nodes improve the availability and reduce the response time and the cost incurred.